1990
DOI: 10.1007/bf01272765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotoninergic drugs on stress-induced hyperthermia (SIH) in mice

Abstract: Summary. 8-OH-DPAT (2.5-10mg/kg) and buspirone (10 mg/kg) but not 5,7-DHT (200 gg/mouse), pCPA (75 and 150 mg/kg, three times), ritanserin (0.1 and 0.2mg/kg), LY 53857 (1.5 and 3mg/kg), GR38032F (0.1-100gg/kg), TFMPP (5 and 20mg/kg) and mCPP (2.5 and 5mg/kg) antagonized the rise in body temperature that occurs to the last mice removed from their group housing, which was termed as stress-induced hyperthennia (SIH). Ro 15-1788, at a dose which blocked the effect of diazepam on SIH, did not reverse the anxiolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Age and sex-matched groups of young adult mice (littermates to the extent possible) were evaluated using a battery of standardized behavioral tests related to “depression and anxiety-like” features by trained staff who were blind to genotype. These included the forced swim test [Porsolt et al, 1977; Sanchez and Meier, 1997], marble burying [Broekamp et al 1986; Witkin, 2008], the open field test [Bouwknecht and Paylor, 2002; Bouwknecht et al, 2004a,b], stress-induced hyperthermia [Lecci et al, 1990; Olivier et al, 1998; Bouwknecht and Paylor, 2002; Bouwknecht et al, 2004a,b], and tail suspension test [Bernardi et al, 1989; Crowley et al, 2004; Cryan et al, 2004]. The methods for the forced swim test and marble burying test are described below, while the methods and results for the remaining tests are described in the supplementary online materials and at www.psychogenics.com.…”
Section: Methodsmentioning
confidence: 99%
“…Age and sex-matched groups of young adult mice (littermates to the extent possible) were evaluated using a battery of standardized behavioral tests related to “depression and anxiety-like” features by trained staff who were blind to genotype. These included the forced swim test [Porsolt et al, 1977; Sanchez and Meier, 1997], marble burying [Broekamp et al 1986; Witkin, 2008], the open field test [Bouwknecht and Paylor, 2002; Bouwknecht et al, 2004a,b], stress-induced hyperthermia [Lecci et al, 1990; Olivier et al, 1998; Bouwknecht and Paylor, 2002; Bouwknecht et al, 2004a,b], and tail suspension test [Bernardi et al, 1989; Crowley et al, 2004; Cryan et al, 2004]. The methods for the forced swim test and marble burying test are described below, while the methods and results for the remaining tests are described in the supplementary online materials and at www.psychogenics.com.…”
Section: Methodsmentioning
confidence: 99%
“…Despite being non-significant and given the small sample size further investigation of 1080 + BS coformulations is probably warranted, especially as BS administered alone appeared not to suppress activity, as was the case for DZ (Marks et al 2000). BS was used successfully to treat stressinduced hyperthermia (SIH) in silver foxes at the same dose used in this trial Bakken 1997, 1998) and similar anxiolytic drugs have also been shown to inhibit SIH in laboratory rodents (Lecci et al 1990;Borsini et al 1993). The prevention of SIH by DZ and BS in foxes strongly suggests that anxiety can be managed successfully in foxes by both drugs.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the original SIH paradigm involved group‐housed mice, with those removed last from the home cage displaying elevated body temperature compared to those removed first (Borsini, Lecci, Volterra, & Meli, ). This “cohort removal” phenomenon has been proposed as a model of anticipatory anxiety and is prevented by anxiolytics and enhanced by anxiogenics (Lecci, Borsini, Mancinelli, et al, ; Lecci, Borsini, Volterra, & Meli, ). Cohort removal, however, does not impact EPM performance in mice (Rodgers et al, ).…”
Section: Discussionmentioning
confidence: 99%